Lizbona. Miasto międzykulturowych przepływów .......... 335 - Banaszkiewicz, Magdalena; Golemo, Karolina; Duda, Anna; Czech, Franciszek; Banaś, Monika (Peregrynacje międzykulturowe: Księga jubileuszowa dedykowana prof. Tadeuszowi Palecznemu, 2025)
LISBON: A CITY OF INTERCULTURAL FLOWSThe topic of the essay is the intercultural nature of Lisbon in its various dimensions. The text highlights the cultural influences that have shaped the identity of the city and its mosaic-like character. Lisbon’s unique genius loci stems from its centuries-long history, during which different cultures succeeded one another, met, and clashed. Intercultural Lisbon is primarily shaped by its inhabitants: locals and newcomers from various parts of the world. Their presence in the urban space, their agency, and their creativity continually shape and transform the city. Lisbon’s interculturality is particularly manifested through music, which may serve as a key to understanding the Portuguese capital. The essay combines insights from academic research with the author’s personal reflections on the intercultural spaces in Lisbon.